Implementation features of the microstrip filters with traveling wave ring resonators - Glushechenko E. N. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2012)
The article prsents a block diagram of a traveling wave directional filter, and a system of analytic expressions which defines the levels of the signals in the filter branches. Implementation features of the filter in the microstrip design are considered. The block diagram of such filter, its base topology and signal system are given.